The Price of Immediacy - CHACKO, GEORGE C.; JUREK, JAKUB W.; STAFFORD, ERIK (Journal of Finance, 2008)
ABSTRACT This paper models transaction costs as the rents that a monopolistic market maker extracts from impatient investors who trade via limit orders. We show that limit orders are American options. The limit prices inducing immediate execution of the order are functionally equivalent to bid and ask prices and can be solved for various transaction sizes to characterize the market maker's entire supply curve. We find considerable empirical support for the model's predictions in the cross‐section of NYSE firms. The model produces unbiased, out‐of‐sample forecasts of abnormal returns for firms added to the S&P 500 index.